Impact of global innovation indicator on China’s exports development - Ismail, Hosameldin H. (Edelweiss Applied Science and Technology, 2024)
This research is intended to study the impact of global innovation indicators on Chinese exports development, through describing and analyzing impact the seven innovation indicators on the Chinese exports as well as impact of the key innovation indicator on the Chinese exports, and getting to know the concept of innovation, types of innovation , as well as importance of innovation in achieving economic development, offering job opportunities, contributing to finding innovative solutions for problems, in addition to referring to the seven innovation indicators, which are institutions, human capital, research, infrastructure, market development, business development, knowledge outputs and creative outputs. The research is also intended to study innovation development in China, as China adopted implementation of an innovation-based economic development strategy in 2006, so it took the initiative to set up high- tech zones, technology parks, innovation clusters and funds to support creative projects. China now ranks first worldwide in terms of number of patent applications submitted to the national patent agencies. The Chines government has been keen to increase spending on research, development and innovation to boost exports and thus drive the economic development process. Statistical analysis tools such as simple linear regression, correlation coefficient and coefficient of determination will be used to measure impact of the seven global innovation indicators as independent variables and gross exports as a dependent variable. Outcomes of statistical analysis showed that there is a direct correlation between human capital index and the Chinese researches and exports, while there is no direct correlation between business environment development index and the Chines exports, indicating that business environment in China needs more government efforts to be exerted to improve and develop business environment which includes knowledge businesses, innovation links and knowledge absorption.